RISE AND FALL OF MAMLUK SULTANATE: The Struggle Against Mongols and Crusaders in Holy War - Firdaus, Yelmi Eri; Elfia, Elfia; Meirison, Meirison (Al-Adyan: Journal of Religious Studies, 2020)
For 300 years, precisely from 1250 to 1517, the Mamluk Dynasty ruled in Egypt and Syria. Their power ended after the conquest of the Ottoman Turks, who later built a new empire. The writer wants to describe how the slave nation could become a ruler who gained legitimacy from Muslims. Mamluk is a soldier who comes from slaves who have converted to Islam. "The mamluk phenomenon," as David Ayalon called it, was an extremely large and long-lived important politic, which lasted from the 9th century to the 19th century AD. Over time, Mamluk became a robust military caste in various Muslim societies. Especially in Egypt, but also the Levant, Iraq, and India, mamluks hold political and military power. In some cases, they gained the position of the Sultan, while in other cases, they held regional power as amir or beys. The historical method starts with collecting literature, sorting, and analyzing and interpreting the writer doing historiography on the dynamics of this mamluk dynasty government. A dynasty filled with phenomenon, which originated from slaves and then turned into the ruler of a vast territory. Not only that, but the slaves were also able to defeat big countries like France, Portugal, and Italy. The Mamluk Sultanate was famous for repelling the Mongols and fighting with the Crusaders. They are descended from various variations, but the most frequent is Kipchak Turks, depending on the period and region in question. When a mamluk is bought, their status is above ordinary slaves, who are not permitted to carry weapons or carry out specific tasks. In places like Egypt, from the Ayyubid dynasty to the era of Muhammad Ali of Egypt, Mamluk is considered as "real rulers" with social status over those born as Muslims.Selama 300 tahun, tepatnya dari tahun 1250 hingga 1517, Dinasti Mamluk memerintah di Mesir dan Suriah. Kekuatan mereka berakhir setelah penaklukan Turki Ottoman, yang kemudian membangun sebuah kerajaan baru. Penulis ingin menggambarkan bagaimana negara budak bisa menjadi penguasa yang mendapatkan legitimasi dari umat Islam. Mamluk adalah seorang prajurit yang berasal dari para budak yang telah memeluk Islam. "Fenomena mamluk," sebagaimana David Ayalon menyebutnya, adalah politik penting yang sangat besar dan berumur panjang, yang berlangsung dari abad ke-9 hingga abad ke-19. Seiring waktu, Mamluk menjadi kasta militer yang kuat di berbagai masyarakat Muslim. Terutama di Mesir, tetapi juga Levant, Irak, dan India, mamluk memegang kekuasaan politik dan militer. Dalam beberapa kasus, mereka mendapatkan posisi Sultan, sementara dalam kasus lain, mereka memegang kekuasaan regional sebagai amir atau lebah. Metode historis dimulai dengan mengumpulkan literatur, menyortir, dan menganalisis dan menafsirkan penulis melakukan historiografi pada dinamika pemerintahan dinasti mamluk ini. Sebuah dinasti penuh dengan fenomena, yang berasal dari budak dan kemudian berubah menjadi penguasa wilayah yang luas. Bukan hanya itu, tetapi para budak juga mampu mengalahkan negara-negara besar seperti Perancis, Portugal, dan Italia. Kesultanan Mamluk terkenal karena memukul mundur bangsa Mongol dan bertarung dengan Tentara Salib. Mereka diturunkan dari berbagai variasi, tetapi yang paling sering adalah Kipchak Turki, tergantung pada periode dan wilayah yang dimaksud. Ketika mamluk dibeli, status mereka di atas budak biasa, yang tidak diizinkan membawa senjata atau melakukan tugas tertentu. Di tempat-tempat seperti Mesir, dari dinasti Ayyubiyah ke era Muhammad Ali dari Mesir, Mamluk dianggap sebagai "penguasa nyata" dengan status sosial atas mereka yang terlahir sebagai Muslim.